Philip F. Esler (ed.), Ancient Israel: The Old Testament in Its Social Context, Minneapolis, Fortress Press, 2006, 420 pp., U$S 35.00.- ISBN 0-8006-3767-4 - Pfoh, Emanuel O. (2007)
Fil: Pfoh, Emanuel O. Universidad Nacional de La Plata; Argentina